Street-Level Bureaucracy in the Digital Age: The Changing Role of Civil Servants in Public Service - Iwan Di Wilayah (MSJ : Majority Science Journal, 2026)
This study examines how digitalization reshapes the roles, discretionary practices, and innovative capacities of street-level bureaucrats in public service delivery. The rapid integration of digital technologies, including e-government systems, artificial intelligence, and data-driven platforms, has transformed traditional bureaucratic work and raised critical questions regarding discretion, professional identity, and service quality. This research employs a qualitative descriptive approach using in-depth interviews, non-participant observation, and document analysis, with data triangulation to ensure validity. Data were analyzed through thematic analysis and constant comparative methods within a socio-technical framework. The findings reveal that digitalization shifts bureaucrats from face-to-face decision-makers to system operators and digital facilitators, while also expanding their roles as intermediaries who assist citizens in navigating digital services. Discretion is not eliminated but reconfigured into three main forms: curtailment, enablement, and continuation. Furthermore, street-level bureaucrats emerge as local innovators who adapt policies and systems to contextual needs. However, digitalization also presents challenges, including reduced human interaction, risks of algorithmic opacity, and potential exclusion of digitally disadvantaged groups. In conclusion, digitalization produces an ambivalent transformation of street-level bureaucracy, requiring a balance between technological efficiency and human-centered governance to ensure inclusive and accountable public services